Kepastian Hukum Pelaksanaan Putusan Verstek Terkait Wanprestasi Perjanjian Kredit Perbankan Terhadap Debitor yang Tidak Diketahui Keberadaannya - William Andrew Sectionardo; Putra Hutomo; Iran Sahril (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
This research analyzes the regulation of the implementation of the execution of verstek decisions related to defaults in banking credit agreements and the legal certainty of the implementation of the execution of verstek decisions related to defaults in banking credit agreements against debtors whose whereabouts are unknown. The research concludes that in regulating the execution of verstek decisions related to defaults in banking credit agreements, it is important to have a credit agreement in the form of an Authentic Deed made by a Notary and Creditors must be careful in submitting collateral seizure applications. Execution can be carried out if the debtor does not comply with the court’s decision after being given a warning for 8 days. However, during the execution, if the debtor’s whereabouts are unknown and the assets have been transferred to another party, the execution cannot be continued, which provides legal uncertainty for Creditors.